UNITEN Smart Programming Apps Using Combination of Robotic and Block Programming (RoBlock) - Mohd Azmi M.S.; Lim K.C.; Mohan P.C.; Kit T.W. (Institute of Electrical and Electronics Engineers Inc., 2023)
Java programming language; Robot programming; Robotics; Block based; Block programming; Block-based programming; JAVA; Programming; Robotic; Robotic and block programming; School programming; Scratch; STEM; Text-based programming; Students